From Apathetic to Participatory: Moral Political Education, the Young People's Path to Democratic Consciousness - Anggraeni, Leni; Syaifullah, Syaifullah; Azis, Abdul; Putra, Tarekh Febriana; Irawan, Hendri; Firdaus, Pipin (Jurnal Moral Kemasyarakatan, 2025)
Does the cultivation of democratic values require contextualization along with the progressiveness of social change? The response to this question can be answered scientifically after an objective measurement of the political moral situation. This study seeks to identify ideal interventions for effective political education to increase political awareness, especially in the contemporary political era in Indonesia. Not only presenting data, this study forms and develops solutions. Thus, this study is filled with various systematic flows to 1) translate political awareness; 2) analyze the phenomenon; 3) propose practical intervention solutions that can help strengthen political awareness. To measure political awareness, using the subject's attitude, interest, and opinion (AIO) measurement model. After the subject's profile is identified, data collection uses a comprehensive scale measurement through 3 (three) methods, namely verbal rating scale (VRS), graphic rating scale (GRS), and numeric rating scale (NRS). The results of the analysis show that the political awareness index is 55.20 out of a maximum value of 100, which indicates conditions that are not in accordance with expectations. To improve it, the ideal intervention is to form political education media that are in accordance with the needs of the subject. The best intervention is to compile digital political education media that utilizes social media. Social media can be considered to have strong potential for political knowledge by providing more opportunities to access political content